1957
DOI: 10.1042/bj0650417a
|View full text |Cite
|
Sign up to set email alerts
|

The biochemistry of aromatic amines. 2. The conversion of arylamines into arylsulphamic acids and arylamine-N-glucosiduronic acids

Abstract: Aromatic amines are known to be metabolized by conversion into acetamido derivatives and oxidation to aminophenols. The aminophenols may be conjugated or further metabolized. In studying the metabolism of 2-naphthylamine by paper chromatography two products were detected which gave the free amine on acidification (Boyland & Manson, 1955). One of these substances could be prepared by treating 2-naphthylamine with sodium glucuronate in aqueous solution and is presumably sodium 2-naphthylamine N-glucosiduronate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…Sulphate conjugation is commonly associated with phenols but it has also been shown to occur with aliphatic alcohols [35,36] and with aromatic amines [37,38]. Ethereal sulphate formation is widely distributed and is believed tobe the most primitive of the detoxication mechanisms.…”
Section: Sulphate Conjugationmentioning
confidence: 99%
“…Sulphate conjugation is commonly associated with phenols but it has also been shown to occur with aliphatic alcohols [35,36] and with aromatic amines [37,38]. Ethereal sulphate formation is widely distributed and is believed tobe the most primitive of the detoxication mechanisms.…”
Section: Sulphate Conjugationmentioning
confidence: 99%
“…It had been recognized very early that 2-naphthylamine per se was not carcinogenic after implantation into the bladder of 8 mice (Bonser et al, 1952) and instillation of 2-naphthylamine into the bladder of one dog (Bonser et al, 1954). Boyland and his colleagues (Boyland et al, 1957) suggested the active urinary pre-carcinogen might be 2 -amino -1 -napthylglucuronide which, when hydrolysed in urine by P-glucuronidase, could release 3,2-amino-i -naphthol, which they postulated was the ultimate reactive carcinogen. This suggestion was discounted at the time, partly because both 2-amino-i-naphthylglucuronide and /-glucuronidase were present in rat urine, yet, as everyone knew, rats "do not develop bladder cancer when dosed with 2-naphthylamine" (Deichmann & Radomski, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of an aryl sulphamate (N4-sulphosulphasomizole, IV) was suspected in rat and dog urine and these compounds (aryl sulphamates) are known metabolites of some aromatic amines in vivo (Boyland, Manson and Orr, 1957;Parke, 1960) and in vitro (Roy, 1960;1961). There are also reports in the Japanese literature of the occurrence in urine of the sulphamates of sulphathiazole (Uno and Veda, 1960), sulphisoxazole (Uno and Kono, 1960), and sulfamethylthiadiazole (Uno and Okazaki, 1960).…”
Section: Metabolism Of Sulphasomizolementioning
confidence: 99%